PENERAPAN DATA MINING METODE APRIORI DALAM ANALISIS KECENDRUNGAN PEMBELIAN KONSUMEN GROCERY SHOP - Erlin Elisa; Tukino Tukino; Koko Handoko (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Wholesale stores are a promising retail business today, judging from the movement of their businesses which are increasingly loved by the public because prices are relatively cheaper compared to supermarkets, supermarkets and minimarkets, this business must be able to meet consumer demand so that they are not inferior to similar businesses, including In managing the placement of types of goods on shelves, so far transaction data has been left unattended without being utilized to obtain new information. This study aims to apply the Apriori algorithm datamining technique in analyzing consumer purchasing tendencies at one of the Grocery Shops in Cipta Asri housing, the method used is an in-depth analysis of customer transactions on data that is already owned and data comes from various sources of information. The results obtained from processing sales transaction data in the form of itemset with the application of the concept of datamining association analysis are known to have a support value of 20% and 80% confidence, the results obtained where the combination of goods that are often purchased with Milk, Rice and snacks with each support value of 22.39 %, 83.33% confidence then Rice, Soft drink and Snack support value of 20.90%, Confidence 73.68%.